2011
DOI: 10.1108/02635571111118279
|View full text |Cite
|
Sign up to set email alerts
|

Information communication technology spending in (2008‐) economic crisis

Abstract: PurposeThe purpose of this paper is to analyze the impact of the recent (2008‐) economic crisis on information communication technology (ICT) spending. The empirical findings are discussed within a broader theoretical framework of technological trends/diffusion and economic cycles.Design/methodology/approachFirst, the paper introduces the innovation diffusion theory and theories of economic cycles. Next, it presents the analyses of the data from official statistics, international agencies and research companie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The following recovery lasted until July 2007 when the mortgage crisis in the USA started, which turned into the economic crisis and brought problems with public finances and the debt crisis. The paper of Rojko et al (2011) analyzed the impact of the 2008 economic crisis on total expenditures and thus also ICT expenditures. They concluded that the crisis reduced total expenditures and thus also ICT expenditures, but affected the ICT market selectively and also much less than other sectors.…”
Section: The Role Of Ict In Economic and Productivity Growthmentioning
confidence: 99%
“…The following recovery lasted until July 2007 when the mortgage crisis in the USA started, which turned into the economic crisis and brought problems with public finances and the debt crisis. The paper of Rojko et al (2011) analyzed the impact of the 2008 economic crisis on total expenditures and thus also ICT expenditures. They concluded that the crisis reduced total expenditures and thus also ICT expenditures, but affected the ICT market selectively and also much less than other sectors.…”
Section: The Role Of Ict In Economic and Productivity Growthmentioning
confidence: 99%
“…For example, in a study of 297 small-medium sized enterprises that adopted ICTs, the researchers found positive relationships between ICTs communicative orientation and the four knowledge creation patterns [44]. Similarly, electronic repositories have been found to be useful tools for facilitating knowledge creation practices and storing knowledge products [45,46]. In a study among 315 employees at a single organization, the results showed that intention to use social media for knowledge seeking and contributing is determined by employees' perceived usefulness of social media [15].…”
Section: Corporate Knowledge Creation: Knowledge Patterns Types and mentioning
confidence: 99%
“…Studies have revealed that three out of five organizations rated strategy execution as poor in their specific organizations. Several studies have suggested that the actual value of a strategy can be effectively implemented (Baqir et al, 2015; Keter, 2015; Rajasekar, 2014; Rojco et al, 2011). Similarly, researchers agree that implementing a strategy is more important than the strategy itself.…”
Section: Theoretical Backgroundmentioning
confidence: 99%